Effectiveness of the Combination of Oxytocin Massage with Baby Massage towards Increasing Breast Milk Production - Elisabeth M. F. Lalita; Dwi Wahyu Sulistyowati; Amelia Donsu; Niluh Nita Silfia; Dian Pratiwi; Agnes Montolalu; Olfie Sahelangi (Poltekkes Kemenkes Palu, 2025)
Background: Postpartum mothers in Indonesia are encountering significant challenges with breastfeeding, resulting in a high rate of early discontinuation due to low milk production. However, the combined therapy of oxytocin massage for mothers and baby massage has demonstrated substantial effectiveness in increasing breast milk production. This innovative approach holds significant promise for preventing stunting in newborns and aligns with the government's efforts to reduce stunting rates. This study aims to combine therapy for mothers and babies, especially oxytocin massage stimulation, together with infant massage, to increase breast milk production. Methods: The study was designed as a quasi-experimental study and included two groups of participants: the experimental group and the control group. The study involved a total of 48 participants, with 24 in each group, and used blocked randomization as the sampling technique. The study measured the increase in breast milk production and conducted an analysis using the Independent sample t-test. Results showed that the experimental group given oxytocin massage with baby massage obtained significant results on increasing breast milk production compared to the control group, with an average difference of 9,917 cc. The independent t-test produced a p-value of 0.001; these results prove that there is a significant difference between the experimental group and the control group. Oxytocin is crucial for transferring breast milk from mother to baby, and baby massage increases the frequency of breastfeeding, stimulating the hormone prolactin to produce breast milk. This intervention can be recommended to postpartum mothers, families as a form of support or to health workers to improve the achievement of exclusive breastfeeding.